Deskripsi Kaidah Qira’at Ibn Kathir Dalam Qira’at Sab’ah - Muhammad Zamroji (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2025)
The Qur'an was revealed in various forms of recitation. In the study of 'ulum al-Qur'an, this is explained in one branch of Qur'anic science, namely the science of qira'at. This branch covers seven qira'at, ten qira'at, and fourteen qira'at. These qira'at are divided into several categories, such as mutawatir, mashur, ahad, etc. One part of the seven qira'at is the qira'ah of Ibn Kathir, which scholars classify as qira'ah mutawatir. He was an Imam qira'ah  from the tabi'in generation who had high authority in the transmission of the recitation of the Qur'an, which has two narrators, al-Bazzi and Qunbul. This study aims to descriptively examine several examples of verses in Surah al-Baqarah that are recited according to the narration of Ibn Kathir. This study is important because some of the qira'ah belonging to Ibn Kathir can influence the meaning of verses and the direction of interpretation. Therefore, understanding farsh al-huruf in Ibn Kathir's qira'ah not only introduces the variety of Qur'an recitations, but also opens up opportunities for developing a broader and more contextual understanding of Qur'anic interpretation. This study uses qualitative research with a descriptive method. This type of research is library research, using a historical approach by examining the process of the emergence of qira'at, its development, and related events. The primary data source is the book Faid} al-Barakat fi sab' al-Qira'at and the secondary data consists of related books, journals, and articles. The results of the study show that Ibn Kathir's qira'ah has distinctive characteristics that differentiate it from other qira'ah, both in terms of the principles of usul al-qira'ah, such as the rules of isti'adhah, basmalah, mad, mim jama', ha' kinayah, two hamzahs in two words, two hamzahs in one word, and in terms of farsh al-huruf.